Heteroporous MoS2/Ni3S2 towards superior electrocatalytic overall urea splitting. Issue 41 (3rd April 2018) - Li, Fang; Chen, Junxiang; Zhang, Dafeng; Fu, Wen-Fu; Chen, Yong; Wen, Zhenhai; Lv, Xiao-Jun
Abstract : The heteroporous MoS2 /Ni3 S2 catalyst exhibits the best activity for urea splitting of all the bifunctional electrocatalysts, including Pt, reported until now. Abstract : The heteroporous MoS2 /Ni3 S2 catalyst exhibits excellent electrocatalytic activity for the overall urea splitting with only a cell voltage of 1.45 V at 20 mA cm −2 in 1 M KOH with 0.33 M urea. This value is the best of all the bifunctional urea splitting electrocatalysts, including Pt, reported to date.